GAMBARAN PERILAKU MASYARAKAT DI DESA PURWOREJO KECAMATAN MODAYAG KABUPATEN BOLAANG MONGONDOW TIMUR TERHADAP INFEKSI SALURAN PERNAPASAN AKUT (ISPA) - Mahendra, I Dewa Agung Ngurah; Ottay, Ronald I.; Sapulete, Margareth R. (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2014)
The Acute Respiratory Infection (ARI) is an acute infection that attacks one or more parts of the nose (upper line respiratory)to the alveoli (bottom line respiratory). This often occurs in infants, primarily when there are a malnutrition andless clean environmental conditions. The purpose of this study was to describe the behaviour of people in rural communities.This study used descriptive study design. This research was conducted in the Purworejo Village, Modayag Sub-District, East Bolaang Mongondow District of the North Sulawesi Province. Total population is 820 patriarchs, and thenumbers of samples are 89 respondents. The samples were selected by using the simple random sampling method. Poolingof data was used by questionnaires. The result of this study showed that of the 89 respondents, 56.8% respondentshad a good knowledge, while 43.2% had poor knowledge, 87.1% had a good attitude, on the other hand, 12.9% respondentshad poor attitude, and 88% had good practice related to the ARI, while 12% had a poor practice. It can be concludedthat the knowledge, attitude and practice related to the ARI in the Purworejo Village of Modayag District, East BolaangMongondow are good.Keywords: Knowledge, Attitude, Practice, and Acute Respiratory Infection (ARI).